The water pivot: transforming unsustainable consumption to valuing water as a resource for life - Bowman, Bryony M.; Abbott-Donnelly, Ian; Barsoum, Jean-François; Williams, Peter; Hunt, Dexter V. L.; Rogers, Chris D. F. (Frontiers in Sustainability, 2023)
Water is a resource essential for all life and on which society depends but undervalues. This paper presents theories on methods to pivot from linear, extractive uses of water to considering water as a high value, circular resource. Analysis of the literature, which is primarily focused at the abstractor scale, has highlighted the prioritisation of human water rights over environmental needs without incorporating the ramifications of environmental degradation and the complexities of applying a market-driven approach to a heterogeneous resource particularly at the domestic consumer level. A discussion of the relationship between society and water, in particular mechanisms that have been used to reduce water consumption, highlights the complexity of this issue and the need to consider fairness and equity at the global and local scales. A comparison of global, urban water supply and sanitation costs shows the extensive variation in the amounts of water consumed and the prices paid at the domestic consumer scale. Finally, a series of hypotheses are presented that, with local development, testing and refinement, are posited to bring about change in the value society places on water.